Exploiting Mechanical Instabilities in Soft Robotics: Control, Sensing, and Actuation. Issue 19 (31st March 2021) - Pal, Aniket; Restrepo, Vanessa; Goswami, Debkalpa; Martinez, Ramses V.
Abstract: The rapidly expanding field of soft robotics has provided multiple examples of how entirely soft machines and actuators can outperform conventional rigid robots in terms of adaptability, maneuverability, and safety. Unfortunately, the soft and flexible materials used in their construction impose intrinsic limitations on soft robots, such as low actuation speeds and low output forces. Nature offers multiple examples where highly flexible organisms exploit mechanical instabilities to store and rapidly release energy. Guided by these examples, researchers have recently developed a variety of strategies to overcome speed and power limitations in soft robotics using mechanical instabilities. These mechanical instabilities provide, through rapid transitions from structurally stable states, a new route to achieve high output power amplification and attain impressive actuation speeds. Here, an overview of the literature related to the development of soft robots and actuators that exploit mechanical instabilities to expand their actuation speed, output power, and functionality is presented. Additionally, strategies using structural phase transitions to address current challenges in the area of soft robotic control, sensing, and actuation are discussed. Approaches using instabilities to create entirely soft logic modules to imbue soft robots with material intelligence and distributed computational capabilities are also reviewed. Abstract : Mechanical instabilities provide a novel route to achieve power amplification and attain impressive actuation speeds. An overview of the development of soft robots and actuators that exploit mechanical instabilities to expand their actuation speed, output power, and functionality is presented. These strategies have the potential to address the current challenges in the areas of soft robotic control, sensing, and actuation.